The Influence of Mechanochemical Technology on Anthelmintic Efficacy of Supramolecular Complexes of Fenbendazole with Licorice Extract - I. A. Arkhipov; A. I. Varlamova; S. S. Khalikov; K. M. Sadov; A. V. Dushkin (Российский паразитологический журнал, 2020)
The purpose of the research is studying the effect of mechanochemical technology on anthelmintic efficacy of supramolecular complexes of fenbendazole with licorice extract.Materials and methods. Tests of the supramolecular complexes of fenbendazole (SMCF) with licorice extract (LE) were carried out on 127 heads of young sheep spontaneously infected by Nematodirus sp. and other types of gastrointestinal strongylates. For each helminthosis, animals of different groups of 8–11 animals each were given single oral administration of SMCF with LE in a dose of 2.0 mg/kg in AD in the form of 10 and 17 % powders and 2.4 and 4.5% suspensions in comparison with the basic drug – fenbendazole (FBZ) in a dose of 2.0 mg/kg. SMCF with LE was developed according to mechanochemical technology for 2 hours. The baseline was a group of sheep that did not receive the drug. The anthelmintic efficacy of the preparations was taken into account according to the results of coproovoscopic studies of sheep by flotation before and 16 days after the preparations were used. Accounting for the effectiveness of drugs was carried out according to the "control test" type.Results and discussion. SMСF with LE in a dose of 2.0 mg/kg by AD in the form of 10 and 17% powders and 2.4 and 4.5% suspensions showed respectively 89.2; 83.12; 82.09 and 83.59% effectiveness against Nematodirus spp. and 88.73; 67.3; 83.87 and 86.38% activity against other types of Strongylata when receiving 22.7 and 21.9% effect of the base drug – FBZ.